Taxonomic Diversity of Pico-/Nanoeukaryotes Is Related to Dissolved Oxygen and Productivity, but Functional Composition Is Shaped by Limiting Nutrients in Eutrophic Coastal Oceans - Wang, Yaping; Li, Guihao; Shi, Fei; Dong, Jun; Gentekaki, Eleni; Zou, Songbao; Zhu, Ping; Zhang, Xiaoli; Gong, Jun (Frontiers in Microbiology, 2020)
Pico-/nanoeukaryotes (P/NEs) comprise both primary producers and bacterial predators, playing important biogeochemical and ecological roles in the marine microbial loop. Besides the difference in size, these small-sized fractions can be distinguished from microplankton by certain functional and ecological traits. Nevertheless, little information is available regarding patterns of their taxonomic and functional diversity and community composition along environmental gradients in coastal marine ecosystems. In this study, we applied high-throughput sequencing of 18S rRNA gene to assess the taxonomic species richness and community composition of P/NEs in surface waters of Bohai Sea and North Yellow Sea, northern China spanning a 600-km distance during summer and winter of 2011. The richness of operational taxonomic units (OTUs) formed a U-shaped relationship with concentration of chlorophyll a (Chl-a, a proxy of primary productivity), but a stronger, negative relationship with concentration of dissolved oxygen (DO). These two factors also significantly co-varied with the OTU-based community composition of P/NEs. The effect of geographic distance on community composition of P/NEs was negligible. Among the three functional groups defined by trophic traits, heterotrophs had the highest OTU richness, which exhibited a U-shaped relationship with both DO and Chl-a. The community of P/NEs was dominated by heterotrophs and mixotrophs in terms of read numbers, which showed a trade-off along the gradient of phosphate, but no significant changes along DO and Chl-a gradients, indicating functional redundancy. Similarly, the proportion of phototrophs was significantly and positively correlated with the concentration of silicate. Our results indicate that taxonomic and functional composition of P/NEs are decoupled on a regional scale, and limiting nutrients are important factors in modulating functional composition of these microorganisms in the studied area. These findings contribute towards gaining a better understanding of how diversity of small eukaryotes and their functions are structured in coastal oceans and the effect of environmental changes on the structuring process.